New Bottle for Milk: An Approach towards Positive and Negative Aspects - Kirill Voinov (Current Approaches in Science and Technology Research Vol. 2, 2021)
In this paper one new way how to surmount foregoing challenges will be described. The standard bottle and carboy shapes are well-known to us. They typically have a two-part shape, which is cylindrical (below) and conical (above) [1-3]. And we grew accustomed to it. Evidently, this is a very easy way to consume drinks (water, milk, cream, mayonnaise, beer, juice, oil, kefir and so on). I’m not interested in debating it. But...Every thing, in practice, has both positive and negative aspects [4]. There are at least two significant negative influences, in my view. For starters, because of the conical shape of bottles, we lose usable space that we can’t use in practice. We are unable to tightly position one bottle on top of the other along the bottle’s height (conical part disturbs us).The following is the second negative and significant event. Because of the conical shape of the container, there is typically a room in the narrow section where good goods can be stored without being used as food. The adhesion for products doesn’t play any negative role at all. Thin edible film helps us to save both products in full and keep the inner wall of bottle having rectangular or square shape clean too.